(untitled) (Progressive Agriculture, 2020)
Twenty-two morpho-agronomic traits of 42 jute genotypes, including 4 varieties with 38 accessions of C. capsularis were evaluated to assess the extent and patterns of variability and their relationships. Seed traits exhibited a wider range of variation than fiber traits. Qualitative traits were also the most informative. Considerable ranges of variability were observed in stem colour, petiole colour, stipule colour, plant technical height, base diameter, dry fibre weight and dry stick weight. Based on major yield contributing characters’ accessions 628, 633, 635 and 646 performed better in most of the cases than the control variety CVL-1, CVE-3, BJC-7370 and BJC-83. Progressive Agriculture 31 (1): 10-18, 2020